Beyond the Bedside: Can AI Predict Patient Deterioration with Precision? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2024)
The subtle, often fleeting, signs of a patient's clinical decline are a critical challenge in modern healthcare. Traditional methods, such as the National Ea...
Keywords: Digital Health; Artificial Intelligence; Healthcare Innovation; Patient Care; Machine Learning